625 The Impact of COVID-19 on Burn Care at a Regional Burn Center - Rogers, Alan D (J Burn Care Res, 2021)
INTRODUCTION: The COVID-19 pandemic has had a profound global impact, not least on hospital functioning. Institutions have all had to prepare and adapt to a large number of admissions, and the influence on elective and emergency surgical services, including burn care, has been significant; it may be some time before we know the full extent of this. While many centers were able to commence more normal activities for a while, we are now seeing an exponential rise in cases again, with potentially catastrophic consequences for the provision of burn care. METHODS: A review of all admissions, operative cases and clinic visits between 1 April and 31 August 2020 was undertaken at an American Burn Association verified burn center. These data were compared with the same five-month period in the preceding two years. RESULTS: Selected data highlights are tabulated (Table 1). During the five months in question, fewer patients were admitted than the previous two years (N=81 versus 121). The mean total body surface area was slightly higher this year (13.7%), and the mean length of hospital stay longer (18 days). The male-to-female ratio of admitted patients was greater during the five months of 2020, at 2.9:1, compared to 1.7:1. No significant differences in terms of etiology were detected, however. As expected, clinic visits reduced dramatically from a mean of 160 patient visits per month to just 81 per month, with the majority conducted virtually. During 2020 the operative cases were similar in number to previous years (N=176), but the mean duration was significantly longer (190 minutes). The total time utilised for burn surgery was similar to previous years (572 hours). [Image: see text] Table 1. Selected burn center data comparing 2020 with 2019 and 2018. CONCLUSIONS: This study demonstrates that although total admissions were slightly reduced, the demands on Burn ICU bed resources and burn operating time were similar. The data supports the notion that removing scheduled operating time for our service resulted in less efficient execution of acute burn surgeries and longer hospital stays. Although formal clinic visits were significantly reduced and were mainly conducted virtually, several patients were satisfied by a novel and user-friendly email service conducted by our clinic nurse specialist.